Route Optimization for Bus Dispatching Based on Genetic Algorithm-Ant Colony Algorithm - Minan Tang; Enen Ren; Chunyan Zhao (2009 International Conference on Information Management, Innovation Management and Industrial Engineering, 2009)
On account of route optimization of bus dispatching, it is proposed to use genetic ant algorithm (GAA) for solution. A mathematic model for multi-objective bus route optimization and selection under limited conditions is developed, introducing the evolutionary process of genetic variation to improve the optimization of ant colony algorithm and also the optimal decision updating and identification in the course of random search of colony to improve the optimization performance and speed up convergence, thus allowing the algorithm with randomicity and determinacy. As a result, the solving steps of the algorithm are given in details. Through comparison of the example results, the algorithm is proved to be feasible and practical for route optimization of bus dispatching.